Cannabinoids – the possible use in palliative medicine - Dzierżanowski, Tomasz (Medycyna Paliatywna/Palliative Medicine, 2018)
The interest in the use of cannabinoids in palliative care has increased in recent years. Their multi-directional action, although of limited effectiveness, makes them an attractive alternative, especially in patients with multiple concomitant symptoms. There is evidence of the effectiveness of cannabinoids in indications such as pain, spasticity, seizures, sleep disorder, nausea and vomiting, and Tourette syndrome. Although the effectiveness of pain management is limited, it is evident in neuropathic pain and the adjuvant treatment along with opioids. Due to their favorable adverse effects profile and lack of depressive impact on the respiratory system, cannabinoids can supplement the relatively narrow set of medicines at the disposal of the palliative medicine physician.